Comparison of Ki-67 equivalent antibodies. Issue 6 (1st June 2002) - Lindboe, C F; Torp, S H
Abstract : Aims: To compare commercially available Ki-67 equivalent antibodies with regard to qualitative and quantitative immunohistochemical staining characteristics. Methods: The following antibodies were used: monoclonal MIB-1 (Immunotech), monoclonal MM1 (Novocastra), polyclonal NCL-Ki-67p (Novocastra), and polyclonal Rah Ki-67 (Dako). All immunostainings were evaluated in squamous epithelium from formalin fixed and paraffin wax embedded pharyngeal tonsils. Labelling indices (LIs) were recorded twice to test their reproducibility. Results: By application of all four antibodies the nuclear staining could be either diffuse, granular, or a combination of both (classified as granular in this study). The diffuse pattern generally showed a strong or moderate staining intensity, whereas the granular pattern displayed a continuum from strong to very weak, making it difficult to discriminate between positive and negative nuclei. The diffuse staining pattern was seen in approximately 59% of the nuclei with the MIB-1 antibody and in 35–45% when the other antibodies were used. The following mean LIs were recorded: MIB-1, 31%; NCL-Ki-67p, 21%; Rah Ki-67, 17%; and MM1, 14%. The reproducibility was excellent for all four antibodies, with the mean of differences between the two runs of counts ranging from 1.1% to 1.5%. Conclusions: The four tested Ki-67 equivalent antibodies revealed differences in qualitative and quantitative staining characteristics, which resulted in considerable variations in registered LIs. The MIB-1 antibody appears to have a higher sensitivity for detecting the Ki-67 antigen than the other three tested antibodies. These differences are important to consider when proliferative activity is determined by the Ki-67 LI.